Analisis Keterampilan Berbicara pada Pembelajaran Bahasa Indonesia Siswa Kelas IV MIS Istiqomah Al-Ulya Desa Payageli - Puspita, Anggun Dela; Balqis, Annisa; Syakira, Fitri; Arisqo, Windi Putri (Lembaga Yasin AlSys, 2023)
The purpose of the research in this preliminary study is to (1) know the speaking skills of class IV in MIS Istiqomah Al-Ulya Payageli (School, (2) find out the factors that affect the speaking skills of class IV, (3) find out solutions to improve the speaking skills of fourth grade students. The method in this research is descriptive with the type of case study research. The analysis techniques used in this study are qualitative and quantitative. Timing of data collection begins on Juny 20, 2023 until completion. The subjects in this preliminary study were 23 students in grade IV and 1 in class IV in MIS Istiqomah Al-Ulya Payageli. The observations showed that it was difficult for students to convey verbally about stories that had been known before, the implementation of the learning method was not in accordance with the material being studied. The test results state that 3 students get grades above the KKM out of a total of 23 grade IV students, with the KKM determined by the school that is 70, the data shows that there are 20 students who score below the KKM so that the average value of students is 62. Drawing conclusions in the preliminary study this can be said that the learning methods applied to Indonesian language learning are not appropriate so that students' speaking skills have not been maximally achieved.